Palestinian commemoration in Israel : calendars, monuments, and martyrs - Sorek, Tamir (Stanford studies in Middle Eastern and Islamic societies and cultures, 2015)
"Palestinian commemorations in Israel are uniquely tied to Palestinian encounters with the Israeli state apparatus, with Jewish Isaeli citizens of Israel, and by the position of Palestinians as Israeli citizens. Reflecting long- standing tensions between Palestinian citizens and the Israeli state, as well as growing pressures across Palestinian societies within and beyond Israel, these moments of commemoration distinguish Palestinian citizens not only from Jewish citizens, but Palestinians elsewhere. In this book, Tamir Sorek considers the development of collective memory and national commemoration among the Palestinian citizens of Israel. He charts the popular politicization of four key events--the Nakba, the 1956 Kafr Qasim Massacre, the 1976 Land Day, and the October 2000 killing of twelve Palestinian citizens in Israel--and investigates a range of commemorative sites, including memorial rallies, monuments, poetry, the education system, political summer camps, and individual historical remembrance. Ultimately, Sorek shows that Palestinian citizens have developed commemorations and a collective memory that offers both moments of protest and points of dialogue"--Back cover